Seascape ecology in Posidonia oceanica seagrass meadows: Linking structure and ecological processes for management. (April 2018) - Abadie, Arnaud; Pace, Matthew; Gobert, Sylvie; Borg, Joseph A.
Highlights: Natural and anthropogenic factors carve Posidonia oceanica seascapes. Few studies address both structure and function at large spatial scale. Recent mapping methods are relevant to study the structure of seagrass seascapes. Limitations remain at the level of data processing for effective management use. Abstract: Seagrass meadows constitute marine habitats in shallow water temperate and tropical coastal areas worldwide that have a high ecological and economic importance. Amongst the 60 or so seagrass species, the endemic Mediterranean species Posidonia oceanica forms meadows that are arguably the most important shallow water coastal habitat in the region but which are subjected to high anthropogenic pressures. Because of the relatively large size of the plant, the meadows formed by this seagrass have high architectural and morphological complexity, which results in different morphotypes or seascapes. While numerous studies of P. oceanica architectural characteristics for continuous meadows of the seagrass are available, few works have addressed seascape ecological features and the influence of environmental factors (natural and anthropogenic) thereon. In the present review, we give an overview of P. oceanica meadow architectural and morphological characteristics and how these contribute to Mediterranean landscapes and seascapes. Studies addressing the influence of natural and anthropogenic factors on morphometric features of different meadow types and landscape ecological characteristics of P. oceanica habitat are also reviewed, as well as their influence on ecosystem processes. Finally, by considering the available data and tools for seascape studies, we present a discussion on methods to assess seagrass seascapes within the framework of coastal management. Our review highlights several gaps in P. oceanica seascape ecology knowledge such as the lack of data on the spatial distribution of this engineer species, and the possibility to use modern techniques and procedures for analysing structural and ecosystemic data.